Implementation of sustainable forest management at local, regional and global level – selected legal aspects - Leśkiewicz, Katarzyna (Przegląd Prawa Rolnego, 2018)
The aim of the article is to answer the question whether and if so, how the legislator shapes the harvesting of timber in a manner consistent with the objectives of sustainable forest management. The implementation of forest management is strongly influenced by global conditions. At the regional level, the legislator has defined “measures” implemented to counteract the marketing of illegally harvested timber. They are known as the EU’s “due diligence system” used in the timber supply chain “from forest to final purchaser.” At the local level, the instruments to achieve this objective of sustainable forest management include control, supervision and sanctions for breaches of Regulations 995/2010 and 2173/2005, while in practice, it is global market practices and related global conformity assessment systems relating to national forestry legislation that ultimately determine how the principles of the due diligence system will be implemented.